Low dielectric constant materials for multilevel interconnect applications - Wong, Terence Kin Shun. (2008)
Low dielectric constant (low-k) constitutive dielectrics for interconnects have been fabricated by both plasma deposition and solution synthesis from -organosilicon precursors. Fluorinated silicon oxide (FSG) was deposited from an inductively coupled high density plasma. The mechanisms of dielectric constant reduction and moisture uptake at high fluorine concentration were determined. Carbon doped silicon oxide (SiOCH) was deposited by glow discharge plasma from trimethylsilane and the effect of deposition parameters on film properties were systematically studied. Two synthesis routes for nanoporous inorganic-organic hybrid low-k dielectrics were developed. Organically modified nanoporous silica was synthesized by a multiple step sol gel process from two precursors and a dielectric constant of 2 was realized. Nanoporous hydrogen methylsilsesquioxane was prepared by thermal curing of the precursor and a dendrimer sacrificial template followed by thermal decomposition of the template.